Microbial contamination and biofilm formation in ophthalmic solutions and ophthalmic instruments at optometry practice - Abd Karim, Aina Balqis; Ahmad Yusof @ Hanafi, Hanani; Saad Al Saadoun, Aisyah; Abdul Rahim, Muhammad Afzam Shah; Buari, Noor Halilah; Yusof @ Alias, Firdaus (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2024)
Background: Maintaining sterility and preventing microbial contamination are critical in optometry, where multiple surfaces, devices, and solutions contact the patient's eyes, posing an infection risk. Contamination, especially from biofilm-forming pathogens, can occur from airborne droplets, surface contact, and improper disinfection. This study investigates microbial contamination and biofilm formation in solutions and on the surface of ophthalmic instruments commonly used in optometry practices. Methodology: Samples were collected from a university-affiliated optometry practice deemed a centre for clinical practice, teaching, and research. Samples were obtained from the dropper tip's ophthalmic bottles and the bulk solution, repeated for both newly opened bottles and after one month of use. One-time samples from various ophthalmic instruments (slit lamps, trial frames, trial lenses, and occluders) were also collected after clinical usage. Contact lens containers were also sampled from the outer edge of the bottles. All samples were placed on Congo Red Agar (CRA) for microbial analysis. Results: Microbial contamination was observed from the dropper tips of newly opened bottles but not in the solutions. After one month of use, microbial contamination increased from dropper tips but remained absent in solutions. No biofilm formation was recorded before and after one month of use. Ophthalmic instruments exhibited substantial contamination after use, with some showing biofilm formation. Contact lens containers showed contamination without biofilm formation. Conclusion: This study shows bacterial presence on the ophthalmic instruments and solution packaging used in the study location. The most common contamination occurs at the dropper tip while the solution remains pristine. Microbial biofilm observed on ophthalmic tools underscores the importance of diligent sanitation procedures for optometrists.